The photodissociation dynamics of ozone at 193 nm: an O(1D2) angular momentum polarization study. - Brouard, M; Cireasa, R; Clark, A; Groenenboom, G; Hancock, G; Horrocks, S; Quadrini, F; Ritchie, G; Vallance, C (2006)
Polarized laser photolysis, coupled with resonantly enhanced multiphoton ionization detection of O(1D2) and velocity-map ion imaging, has been used to investigate the photodissociation dynamics of ozone at 193 nm. The use of multiple pump and probe laser polarization geometries and probe transitions has enabled a comprehensive characterization of the angular momentum polarization of the O(1D2) photofragments, in addition to providing high-resolution information about their speed and angular distributions. Images obtained at the probe laser wavelength of around 205 nm indicate dissociation primarily via the Hartley band, involving absorption to, and diabatic dissociation on, the B 1B2(3 1A1) potential energy surface. Rather different O(1D2) speed and electronic angular momentum spatial distributions are observed at 193 nm, suggesting that the dominant excitation at these photon energies is to a state of different symmetry from that giving rise to the Hartley band and also indicating the participation of at least one other state in the dissociation process. Evidence for a contribution from absorption into the tail of the Hartley band at 193 nm is also presented. A particularly surprising result is the observation of nonzero, albeit small values for all three rank K = 1 orientation moments of the angular momentum distribution. The polarization results obtained at 193 and 205 nm, together with those observed previously at longer wavelengths, are interpreted using an analysis of the long range quadrupole-quadrupole interaction between the O(1D2) and O2(1Deltag) species.